Analisa Pengukuran Kinerja Korporasi Perusahaan di PT X Dengan Menggunakan Metode Key Performance Indicator - Yoga Anunggita; Tranggono Tranggono (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
In measuring the corporate performance of PT X in the third quarter period, it has not been achieved optimally. This non-achievement is caused by several factors including projects from several corporate divisions in the production section that have not been completed within 1 year, the realization of the Company's Work Plan and Budget Year 2023 which is not optimal, and performance management by each corporate leader that is not optimal. Therefore, it is necessary to measure the company's corporate performance using the Key Performance Indicator method to determine performance measures in Quarter III. The research conducted uses information obtained from observations and data sources directly from the company. Then data processing using the Key Performance Indicator method to determine the achievement of the company's corporate performance. From the results of the achievement of each indicator, the total score of the company's corporate Key Performance Indicator in the third quarter of 2023 was 46.45%. For the Key Performance Indicator target based on the Company's Work Plan and Budget of 100%. Therefore, the achievement of the realization of the Key Performance Indicator score on the company's corporate performance has not met the target in the Company's Work Plan and Budget for 2023. So it is necessary to accelerate the realization of indicators that have not met the achievement of performance based on the Company's Work Plan and Budget Year 2023.